(untitled) - White, Linda Arms.; Curry, Tom (New York, 2000)
While visiting their mother's ranch, two brothers who constantly try to best each other swap tall tales about big winds and are surprised by the fiercest wind they have ever seen.
Keywords: Tall tales; Fiction; Fiction; Winds; Brothers